1994
DOI: 10.1152/jappl.1994.76.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Strength training increases resting metabolic rate and norepinephrine levels in healthy 50- to 65-yr-old men

Abstract: Resting metabolic rate (RMR) decreases with age, largely because of an age-related decline in fat-free mass (FFM). We hypothesized that a strength-training program capable of eliciting increases in FFM would also increase RMR in older individuals. To test this hypothesis, RMR, body composition, and plasma concentrations of certain hormones known to affect RMR were measured before and after a 16-wk heavy-resistance strength-training program in 13 healthy men 50-65 yr of age. Average strength levels, assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
166
3
12

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(202 citation statements)
references
References 0 publications
17
166
3
12
Order By: Relevance
“…Resistance training is a powerful stimulator of sympathetic nervous system activity, which may intensify vasoconstriction through a sympathetic adrenergic vasoconstrictor effect. 27,28 Sympathetic nervous activity during ECC muscle activity has been shown to be lower than that during CON muscle activity. 29 Although sympathetic nervous activity was not measured in this study, it may have contributed to the increased arterial stiffness, because low muscle sympathetic nerve activity caused by ERT suppresses the vascular smooth muscle tension level.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training is a powerful stimulator of sympathetic nervous system activity, which may intensify vasoconstriction through a sympathetic adrenergic vasoconstrictor effect. 27,28 Sympathetic nervous activity during ECC muscle activity has been shown to be lower than that during CON muscle activity. 29 Although sympathetic nervous activity was not measured in this study, it may have contributed to the increased arterial stiffness, because low muscle sympathetic nerve activity caused by ERT suppresses the vascular smooth muscle tension level.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest an increase of 6.8 to 7.7% in the resting energy expenditure after 12 to 16 weeks of weight training in adults and older individuals (27)(28) . Ballor and Poehlman (29) observed in meta-analysis that the resting energy expenditure seems to be proportional to the metabolic active tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, the explanations for the increase in the total and resting energy expenditure can also be related, besides the muscular mass increase, to the exercise intensity, to the increase in the metabolic activity of the lean tissue as well as to the increase in the basal concentrations of noradrenaline (23,27) .…”
Section: Discussionmentioning
confidence: 99%
“…Whether endurance training influences resting metabolic rate after adjustment for body composition is still controversial. Some studies have shown an increase in resting metabolic rate, adjusted for fat-free mass and fat mass, in response to training [7][8][9] whereas others found no effect. [10][11][12] In contrast to these studies, not much research has been focused on establishing the most beneficial exercise intensity for increasing 24 h energy expenditure 24 h EE.…”
Section: Introductionmentioning
confidence: 99%